Coptis inhibited epithelial–mesenchymal transition and fibrogenesis of diabetic nephropathy through lncRNA CLYBL-AS2-miR-204-5p-SNAI1 axis. (20th October 2020) - Cai, Shengyu; Liu, Juan; Ma, Qingyu; Bao, Yuxiao; Chen, Jiaxu; Li, Yousheng
Abstract: Diabetic nephropathy (DN) is one of the severe complications of diabetes. Nowadays, effective treatment for end-stage renal disease (ESRD) patients is still limited. HK-2 cells were stimulated with serum from phosphate-buffered saline (PBS) or Jiawei Shuilu Erxiandan (JSE)-treated DN mice, then long non-coding RNA (lncRNA) CLYBL-AS2 was discovered by RNA sequence, following the comparison of the serum from normal patients with DN patients to confirm the role of lncCLYBL-AS2. Next, we performed in vitro studies to explore the effect of lncCLYBL-AS2 in DN and its molecular mechanism. Coptis, as one of the components of JSE, could decrease the expression of lncCLYBL-AS2, which is increased in DN and correlated with the severity of DN. Knockdown/overexpression of lncCLYBL-AS2 inhibited/promoted the invasion and fibrogenesis of HK-2 cells. Furthermore, lncCLYBL-AS2 was negatively correlated with miR-204-4p with a positive correlation with SNAI1; eventually, CLYBL-AS2 regulated SNAI1 by binding to miR-204-5p, which accounted for the inhibition of epithelial–mesenchymal transition (EMT) and fibrogenesis. LncCLYBL-AS2 inhibited by Coptis improved EMT and fibrogenesis in HK-2 cells through miR-204-5p-SNAI1 axis, therefore, lncCLYBL-AS2 could serve as a potential diagnosis and therapeutic target for DN.